Tradução colectiva - Guimarães, Brigith; Pires, Carla Morais; Leal, Gisela; Figueiredo, Julita; Osório, Jorge Miguel; Carvalho, Vera (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
.